ECHINODERMATA, Holothuria atra, IN AN INTERTIDAL SEAGRASS BED OFF THE BAMA BEACH, BALURAN NATIONAL PARK, EAST JAVA, INDONESIA - Ana Setyastuti (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
The occurrence of sea cucumber, Holothuria atra, was assessed in the seagrass area of the Bama beach, Baluran National Park in East Java. The study investigated the frequency and early stages of seagrass association preference of H. atra. Survey was conducted in May 2011 using belt transect (1m x 100m with three replicates). Frequency of H. atra and their association with seagrass were recorded. Furthermore, length and wet weight of each individual of H. atra were measured. The total of 146 individuals of H. atra were observed in which 37.67% associated with Enhalus acoroides (EA), 23.29% associated with Cymodocea rotundata (CR), 23,29% associated with mixed seagrass species of E. acoroides and C. rotundata, and 15.75% associated with no seagrass habitats. The results suggested that small size H. atra might prefer to live under the taller seagrass stands such E. acoroides, which could be morphologically benefits the H. atra by providing better protection and shelter area. Keywords: Holothuria atra, Enhalus acoroides, Cymodocea rotundata, Baluran National Park